Pleasant Dreams or Nightmares, in the Public Debts Scenarios? - Vito Tanzi (ifo Schnelldienst, 2016)
– Vortrag von Prof. Vito Tanzi former Director of the Fiscal Affairs Department of the IMF and a former Undersecretary for Economy and Finance in the Italian Government
Keywords: H63; E62; 330; Öffentliche Schulden; Finanzpolitik